Occurrence of endocrine-disrupting chemicals (EDCs) in river water and sediment of the Mahakam River - Hadibarata, Tony; Kristanti, Risky Ayu; Mahmoud, Ahmed Hossam (IWA Publishing, 2020)
The study was performed to examine the occurrence of endocrine disrupting chemicals (EDCs), including four steroid estrogens, one plasticizer, and three preservatives in the Mahakam River, Indonesia. The physicochemical analysis of river water and sediment quality parameters were determined as well as the concentration of EDCs. The range of values for pH, total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD), total suspended solids (TSS), nitrate, ammonium, phosphate, and oil/grease in river water and sediment were higher than recommended limits prescribed by the World Health Organization's Guidelines for Drinking-water Quality (GDWQ). Bisphenol A (BPA) was the most widely found EDC with the highest concentration level at 652 ng/L (mean 134 ng/L) in the river water and ranged from ND (not detected) to 952 ng/L (mean 275 ng/L) in the sediment. Correlation analysis to investigate the relationship between the EDCs' concentrations in water and sediment also revealed a significant correlation (R2 = 0.93) between the EDCs' concentrations. High concentrations of EDCs are found in urban and residential areas because these compounds are commonly found in both human and animal bodies, resulting in the disposal of EDCs into canals and rivers in urban and suburban areas, as well as livestock manure and waste that is generated from intensive livestock farming around the suburban area.